Sustainability report editorials: A predictive signal for a company’s inclusion in a sustainability index? - Bernard, Yohan; Godard, Laurence; Herve, Fabrice; Zouaoui, Mohamed (Management international / International Management / Gestiòn Internacional, 2023)
This study examines whether references to Corporate Social Responsibility (CSR) in the editorials of sustainable development reports have any predictive influence with respect to firms’ inclusion in the Dow Jones Sustainability World Index (DJSWI). Signalling theory proposes hypotheses that can be tested by textual analysis of sustainable development report editorials published by French firms. The results suggest that these editorials may serve as leading indicators of CSR. The predictive power of editorials is strengthened when they are signed by the Chief Executive Officer (CEO), published in a sustainability report and written in a clear and readable style.